Rumah Persulukan Tuan Guru Musa: Studi Tentang Interaksi Agama di Kabupaten Labuhanbatu Utara - Susilawati; Rholand Muary (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Rumah Persulukan Tuan Guru Musa serves as a central hub for religious and cultural learning, playing a crucial role in shaping the local community's culture. Within this